Predictive Value of Albumin to Fibrinogen Ratio and CALLY Index for Diagnosis of Ulcerative Colitis and Mucosal Healing After Vedolizumab Treatment - Su K; Xiao S; Wang M; Wang K; Fan Q; Sha S; Cheng Y; Liu X; Shi H (Journal of Inflammation Research)
Kairong Su,1,* Sinan Xiao,1,* Mei Wang,2 Kairuo Wang,1 Qing Fan,1 Sumei Sha,1 Yongli Cheng,3 Xin Liu,1 Haitao Shi1 1Department of Gastroenterology, The Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Department of Gastroenterology, Xi’an International Medical Center Hospital, Xi’an, Shaanxi, People’s Republic of China; 3Department of Gastroenterology, Xi’an Chang’an District Hospital, Xi’an, Shaanxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Liu, Department of Gastroenterology, the Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China, Email docliuxin126@xjtu.edu.cn Haitao Shi, Department of Gastroenterology, the Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China, Email shihaitao7@xjtu.edu.cnPurpose: The albumin to fibrinogen ratio (AFR), a biomarker associated with inflammatory, nutritional, and coagulation status, and the CALLY index, a biomarker combining C-reactive protein, albumin, and lymphocyte count, have been suggested to correlate with prognosis in a variety of diseases in previous studies; however, studies of these two markers in ulcerative colitis (UC) are lacking. The aim of this study was to evaluate the clinical significance of AFR and CALLY index in UC.Methods: The study included 109 UC patients and 126 healthy controls. For UC patients treated with Vedolizumab (50 patients), they were categorized into mucosal healing group (MH group) and non- mucosal healing group (non-MH group) based on Mayo endoscopic score (MES) after 14 weeks of treatment. The differences in AFR and CALLY index were compared between the UC group and the healthy control group, and between the MH group and the non-MH group. Then, the correlation of the AFR and CALLY index with UC activity was assessed, and the predictive value of the AFR and CALLY index was evaluated using the receiver operating characteristic (ROC) curve.Results: The results showed that both AFR and CALLY index were significantly decreased in the UC group compared with the healthy control group (both p< 0.001); the area under the curve (AUC) of the AFR and CALLY index differentiating between the healthy control group and the UC group were 0.782 and 0.773, respectively. For Vedolizumab treatment, the non-MH group had significantly lower baseline AFR and CALLY index compared to the MH group; the AUC for baseline AFR and CALLY index discriminating the MH group from the non-MH group were 0.665 and 0.721, respectively. In addition, AFR and CALLY index were negatively correlated with the MES and inflammatory load of UC. The results of multivariate logistic regression analysis showed that the CALLY index was an independent predictor of UC diagnosis and mucosal healing after 14 weeks of Vedolizumab treatment.Conclusion: AFR and CALLY index can be used as novel serologic markers for diagnosing UC and predicting the efficacy of Vedolizumab treatment.Keywords: albumin to fibrinogen ratio, CALLY index, ulcerative colitis, Vedolizumab, mucosal healing, biomarkers